The Role of Knowledge Sharing, Learning Organization and Transformative Leadership in Building Competitiveness - Gideon, Andrea (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
An organization’s performance can be measured using financial and non-financial approaches. If financial and non-financial management has been managed effectively and efficiently, this can be one of the benchmarks. The ability to be able to carry out management effectively and efficiently needs to be complemented by knowledge. The ability of an organization to continuously learn and develop its capacity is what every organization must have. Organizations must continue to process in gathering knowledge. This ability must be accompanied by transformational leadership capable of bringing about change for the realization of the organization’s vision. This type of leadership helps raise employee awareness and deepen their level of perception and acceptance of the group’s vision and goals. Transformational leadership changes employees through words and actions and deeply influences followers. In addition, the ability to share the knowledge that has been obtained is expected to increase the influence of the organization’s ability to gather knowledge and the influence of transformational leadership on organizational performance. This research takes the object of SMEs in the field of tourism, meaning those who produce work or souvenirs for tourism purposes. the ability to share the knowledge that has been obtained is expected to increase the influence of the organization’s ability to gather knowledge and the influence of transformational leadership on organizational performance. This research takes the object of SMEs in the field of tourism, meaning those who produce work or souvenirs for tourism purposes. the ability to share the knowledge that has been obtained is expected to increase the influence of the organization’s ability to gather knowledge and the influence of transformational leadership on organizational performance. This research takes the object of SMEs in the field of tourism, meaning those who produce work or souvenirs for tourism purposes.